The Characteristics of Five Ceramics and Two Granites as Solid Dielectrics for An Ozone Generator: The Characteristics of Five Ceramics and Two Granites as Solid Dielectrics for An Ozone Generator - Murdiya, Fri; Hardiwika, Ericko (International Journal of Electrical, Energy and Power System Engineering, 2020)
The utilization of ozone is commonly applied in various fields, for instance, it is used as a disinfectant for water treatment, disinfecting, sterilizing medical devices and preserving foodstuffs. Ozone is a nearly colorless gas with a characteristic odor that can be detected by humans up to 0.01 ppm. It can be produced by the dielectric barrier discharge method,which is generally used as a method of generating ozone supplied by high voltage or also called high voltage plasma generators. High voltage plasma occurs in the dielectric barrier discharge air gap, as a result of the air failed in maintaining its insulator properties. The power supply used in this study is a parallel resonant pushpull inverter using a flyback transformer. Furthermore, this study did not use an additional magnetic loudspeaker and used ceramic dielectrics instead. 5 types of ceramics and 2 different types of granite and combined the range of air gap were used during examination and research. The research indicates that the best plasma was found in ceramics 3, 5, granite 1 and 2 with an air gap of 2mm. The current discharge in ceramic 1 with an air gap of 2 mm was higher than the others. The highest voltage discharge was on granite 2 with an air gap of 2 mm. Ceramics 3, 5, granite 1 and 2 with an air gap of 2mm had better ozone concentrations than ceramics 1, 2 and 4.